Arenig volcanic and sedimentary strata, central New Brunswick and eastern Maine - Poole, W.; Neuman, Robert (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2003)
ABSTRACT Arenig strata in the Napadogan area of the Miramichi Highlands of west-central New Brunswick are similar to those of the Lunksoos anti-clinorial area of eastern Maine. Strata from both areas were deposited in a volcanic back-arc setting upon Cambrian-Tremadoc, deep-water, turbiditic quartzose strata on the northwest-facing Gander margin of Gondwana. Tremadoc southeastward obduction of the Penobscot Arc, formed in the Iapetus Ocean to the northwest of the margin, was followed by local uplift, rift faulting, erosion, and finally by local deposition of late Arenig gravel within the early stages of a subsiding back-arc basin that was related to a younger, northwest-facing, early Arenig-Llanvirn Popelogan Arc lying to the northwest. These strata became overlain by late Arenig marine felsic tuff, sandy and silty tuff and mudstone, coarse textured and many hundreds of metres thick in the Lunksoos area but much finer and only a few metres thick farther from the volcanic centres, in the Napadogan area. During Llanvirn, the strata became covered with deep-water, commonly manganiferous, ferruginous shale-chert in a basin shielded from currents carrying coarse detritus. Arenig strata of the Napadogan area probably developed to the southeast of the main rift-volcanism zone that perhaps extended between the Lunksoos and northeastern Miramichi Highlands during the Arenig. Brachiopods of the Celtic paleogeographic assemblage colonized newly formed shelves flanking islands along the zone. Shell beds developed upon fresh layers of ash in a nutrient-rich environment between episodes of volcanism. These Celtic brachiopods developed in cool waters of high southern latitudes off Gondwana, different from those on the Laurentian margin in warm waters of low southern latitudes.